High Blood Pressure: What You Need to Know - Linda B. Bobroff (EDIS, 2008)
Revised! FCS-8638, a 4-page handout adapted from the NHLBI/NIH fact sheet by Linda B. Bobroff, explains the currently known elements of High Blood Pressure–a condition that affects about one in every three American adults, yet often has no symptoms. Published by the UF Department of Family Youth and Community Sciences, August 2008.